El allanamiento de domicilio con orden judicial, vulnera los derechos humanos de las personas, al no cumplirse con el debido proceso - Agurto Oviedo, Alexis Lorena (2015)
The research work concerns: "The raids on homes by court order violates the human rights of the people, not satisfied with the Due Process", to analyze and understand the paragraph two of Article 66 of the Constitution of the Republic. recognizes and guarantees people the right to a decent life. The numeral 22 of the article, determines the right to inviolability of the home. No, you can enter the address of a person, or carry out inspections or searches without the authorization or without a warrant, except in flagrante delicto, in the cases and manner prescribed by law. The Constitution prohibits entry into private homes except in case of commission of crime, you can pave with court order, which goes to the Prosecutor, with the Agents of the judicial police and for this there is provided a method that determines the Article 482 of the Code of Criminal Integral, finding that the search must be done: 1. The presence of the prosecutor and accompanied by the National Police, no. they can enter not authorized by the prosecutor or the place to be ironed people. 2. If presented the search warrant, the either the owner or inhabitant of the home, workplace or local resists the surrender of the person or things or income or exhibition places or objects that are to inside these places, fiscal or order the destruction of the doors or locks. 3. Practiced the raid, the prosecutor recognized or in the presence of competing agencies raided the premises, weapons, documents and objects related to the offense. This is procedure involving criminal law, however it is not met pursuant to the transcript because the Prosecution and Judicial Police pave homes in the early morning hours arbitrarily disregarding the human rights of people who are in that house raided, and forcing to lie face down on the floor, being targeted with guns and intimidate the family; all these results in the violation of the psychological integrity of the people and especially the right to human dignity enshrined in the regime of good living of Ecuador; inobservándose in these raids due process established by the Code of Criminal Integral, all citizens are seeing that through the news media disclosed the performance of the Prosecutor and police who break into the homes skipping due process judicial proceeding. The theoretical, legal and doctrinal gathering, conducting surveys and interviews yielded widely recognized criteria clear and precise basis of literature, which contributed to the verification of the objectives and the testing of the hypothesis concerning this practice; both the Constitution of the Republic of Ecuador, the Organic Code of Criminal Integral criminalizing the procedure to follow in the raids on homes in criminal matters